Management of glycemic crises in adult patients with diabetes mellitus: Evidence-based Clinical Practice Guideline, Lima - Peru. - Gil-Olivares, Fradis (2021)
The manuscript summarizes the process of elaboration of the Clinical Practice Guide (CPG) for the management of glycemic crises in adult patients with diabetes mellitus of the AUNA Clinic Network. A multidisciplinary team of medical assistants and methodologists carried out the development of the CPG and then there was an external review by a specialist in the field. The Elaboration Group of the CPG (GEG) concluded on 10 PICO questions. A systematic search for CPG, systematic reviews and primary studies was carried out to answer these PICO questions.  To make recommendations we used the "GRADE-Adolopment" methodology and the guidelines of the national regulations. Ten recommendations were made (nine strong and one weak), 18 points of good clinical practice and two flowcharts for management (one for diagnosis and the other for the treatment of glycemic crises), 04 consensus tables on management and 01 table for surveillance and monitoring. The topics covered by the recommendations for the management of glycemic crises were hyperglycemic crises (glycosylated hemoglobin evaluation; b-hydroxybutyrate evaluation; insulin, potassium, 0.9% sodium chloride, phosphorus, sodium bicarbonate treatments) and hypoglycemic crises (carbohydrate administration, monitoring, educational program to avoid reentry)